Heat capacity and thermodynamic functions of nano-TiO2 anatase in relation to bulk-TiO2 anatase. (February 2015) - Schliesser, Jacob M.; Smith, Stacey J.; Li, Guangshi; Li, Liping; Walker, Trent F.; Parry, Thomas; Boerio-Goates, Juliana; Woodfield, Brian F.
Abstract : Graphical abstract: Highlights: Heat capacity data and thermodynamic properties for three TiO2 anatase nanoparticles of different hydration are presented. Water contributions were subtracted to yield thermodynamic properties of bare TiO2 anatase nanoparticles. These thermodynamic properties and those of bulk TiO2 anatase are equal within experimental error. Surface adsorbed water stabilizes the anatase phase in the nano-regime. Abstract: Several conflicting reports have suggested that heat capacities and the thermodynamic properties of materials change as their particle size decreases into the nanoscale. To further investigate this, we have measured the constant pressure heat capacities of three 7 nm TiO2 anatase samples containing varying amounts of surface-adsorbed water using a combination of adiabatic and semi-adiabatic calorimetric methods. These samples have a high degree of chemical, phase, and size purity determined by rigorous characterization. Molar heat capacities were measured from T = (0.5 to 320) K, and data were fit to a sum of theoretical functions in the low temperature ( T < 15 K) range, orthogonal polynomials in the mid temperature range (10 > T > 75 K), and a combination of Debye and Einstein functions in the high temperature range ( T > 35 K). These fits were used to generate C p, m °, Δ 0 T S m °, Δ 0 T H m °, and φ m ° values at smoothed temperatures between (0.5 and 300) K for all hydrated samples. Standard molar entropies at T = 298.15 K were calculated to be 73.868, 66.072, and 63.845 J · K −1 · mol −1 all with a standard uncertainty of 0.002· Δ 0 T S m ° for samples TiO2 · 0.677H2 O, TiO2 · 0.532H2 O, and TiO2 · 0.379H2 O, respectively. These and other thermodynamic values were then corrected for water content to yield bare nano-TiO2 thermodynamic properties at T = 298.15 K, and we show that the resultant thermodynamic properties of anhydrous TiO2 anatase nanoparticles equal those of bulk TiO2 anatase within experimental uncertainty. Thus we show quantitatively that the difference in thermodynamic properties between bulk and nano-TiO2 must be attributed to surface adsorbed water.